2020
DOI: 10.5935/1518-0557.20200030
|View full text |Cite
|
Sign up to set email alerts
|

A review of initial data on pregnancy during the COVID-19 outbreak: implications for assisted reproductive treatments

Abstract: The current outbreak of the novel 2019 coronavirus disease started in China in December 2019 and has since spread to several other countries. On March 25, 2020, a total of 375,498 cases had been confirmed globally with 2,201 cases in Brazil, showing the urgency of reacting to this international public health emergency. While in most cases, mild symptoms are observed, in some cases the infection leads to serious pulmonary disease. As a result, the possible consequences of the COVID-19 outbreak for pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 36 publications
1
43
0
3
Order By: Relevance
“…Reproductive health is a significant public health issue during pandemics [4]; however, there is a limited amount of information on how the novel coronavirus affects pregnant women. Although several studies indicated that pregnant women are no more likely to be at a higher risk of becoming seriously ill from COVID-19 [5], a previous study revealed women experience changes in their bodies that may increase the risk of other illnesses, such as viral respiratory infections [6]. This uncertainty is feeding many pregnant women's anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive health is a significant public health issue during pandemics [4]; however, there is a limited amount of information on how the novel coronavirus affects pregnant women. Although several studies indicated that pregnant women are no more likely to be at a higher risk of becoming seriously ill from COVID-19 [5], a previous study revealed women experience changes in their bodies that may increase the risk of other illnesses, such as viral respiratory infections [6]. This uncertainty is feeding many pregnant women's anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…50 Infection control guidelines in ART centres and laboratories Table 2 below lists recommendation for infection control in ART centres and laboratories to help reduce risk of COVID-19 spreading during procedures. 44,45,[50][51][52][53][54] As SARS-CoV-2 can be present in semen, strict protective protocols should be implemented in handling these specimens. 55 Extreme care should be taken during sperm cryobanking, and samples should be stored in highly secured segregated cryovessels.…”
Section: Guidelines To Art Proceduresmentioning
confidence: 99%
“…While there is no clear evidence supporting vertical transmission, it cannot be ruled out due to COVID-positive placental and fetal membranes and neonates being tested positive after birth. 12,27,50,52,[57][58][59] Immunosuppression and hormonal fluctuation during pregnancy leave women more vulnerable to respiratory pathogens and severe pneumonia. 52 Nevertheless, there is no evidence stating increased susceptibility of COVID-19 in pregnancy.…”
Section: Guidelines To Art Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…From then on, the infection due to the new Coronavirus, called COVID-19, was officially an international emergency (WHO, 2020a). On March 11, 2020, the situation escalated even more, as WHO declared that COVID-19 became pandemic due to its global geographical distribution (Monteleone et al, 2020).…”
mentioning
confidence: 99%